Lefkowitz, Not Out Of Africa - How Afrocentrism Became An Excuse To Teach Myth As History - Van Hartesveldt, Fred (Teaching History: A Journal of Methods, 1997)
Mary Lefkowitz is an established classicist working at Wellesley College. Her interest in Afrocentrism developed as she began to be questioned about the failure of classicists to discuss the significance of African--especially Egyptian--influences in the development of modern Western culture. Of course there are such influences, a fact she does not deny. Nonetheless, as she began to examine the works of Afrocentrists such as Martin Bernal, George G.M. James, and others, she found assertions that seemed indefensible. These included the idea that Aristotle plagiarized much of his philosophy from the library at Alexandria--a library not built until after his death--and that Socrates and Cleopatra were black.